Significance of the analysis of banking and financial performance in the countries of the Western Balkans in the period 2010-2019 - Lutovac Jelena (Megatrend Revija)
The significance of the analysis of banking and financial performance in the countries of the Western Balkans in the period 2010 - 2019. The analysis of the banking and financial sector represents one of the main elements in the development and economy of the economies of many countries. This comes to the fore especially in developing countries, in countries that want to be integrated into stronger economic integrations, in conditions of crises and wars. The banking system is considered to represent one of the basic elements of the market economy. Namely, by centralizing money capital, it collects and transforms savings and deposits of citizens, companies and the state. These funds are used in the further banking process as sources of placement and in this way the smooth flow of money through the payment system is enabled. If we look at the financial sector in the countries of the Western Balkans, then it is evident that it is necessary to monitor the indicators of the financial system. All analyzes indicate that the Covid-19 pandemic has been a major threat worldwide since 2008.